2016
DOI: 10.1039/c5nr09264g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the size dependence on the optical modes of anatase nanoplatelets using STEM-EELS

Abstract: †Electronic supplementary information (ESI) available: Histograms of length and thickness of the platelets; perpendicular component of dielectric function; thickness dependence of perpendicular component of loss function; VEEL spectra of edge-on platelet along c-axis; VEEL spectra of face-on and edge platelets stacks. 2 AbstractAnatase titania nanoplatelets predominantly exposing {001} facets have been reported to have enhanced catalytically properties in comparison to bulk anatase. To understand their unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…96 EELS measurements can provide the evidence for charge transfer from the TiO 2 surface to the O 2 molecule based on disappearance of the vacancy loss feature. 97 Liberti et al combined valence EELS with scanning TEM to obtain the dielectric response of anatase nanoplatelets, 98 and they were able to characterize the complex dielectric properties with superior spatial (<1 nm) and energy (<100 meV) resolution. The authors found that the energies of the symmetric mode and antisymmetric mode shifted toward lower and higher energy-losses, respectively, with decrease in the thickness of the anatase nanoplatelet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…96 EELS measurements can provide the evidence for charge transfer from the TiO 2 surface to the O 2 molecule based on disappearance of the vacancy loss feature. 97 Liberti et al combined valence EELS with scanning TEM to obtain the dielectric response of anatase nanoplatelets, 98 and they were able to characterize the complex dielectric properties with superior spatial (<1 nm) and energy (<100 meV) resolution. The authors found that the energies of the symmetric mode and antisymmetric mode shifted toward lower and higher energy-losses, respectively, with decrease in the thickness of the anatase nanoplatelet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The S signal is strongest at the edges, where the entire primary electron beam trajectory intersects with the surface region; in the center of the NW, the beam only intersects with the upper and lower surfaces. The significant S intensity when the electron beam is aloof (nearby but not intersecting with the nanowire) is likely due to the excitation of surface plasmons, , which decay to excitons and subsequently recombine via surface traps in the ZnO, but may also be caused by stray electrons that directly excite excitons preferentially at the nanowire surface. The peak of S intensity extends into the nanowire due to excitons excited in the nanowire diffusing to the surface, where they subsequently decay.…”
mentioning
confidence: 99%